Pelaksanaan Evaluasi Pembelajaran Kurikulum Merdeka Pada Mata Pelajaran PAI Di UPTD SDN 05 Koto Tangah Batu Hampa - Zakiatul Islamie; Wedra Aprison; Arman Husni; Iswantir M (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research is motivated by several phenomena that teachers do not master the implementation of evaluation in the independent curriculum, which causes evaluation to not be implemented optimally. This research aims to see the implementation of the formative evaluation of independent curriculum learning in PAI subjects at UPTD SDN 05 Koto Tangah Batu Hampa, and to find out the implementation of the summative evaluation of independent curriculum learning in PAI subjects at UPTD SDN 05 Koto Tangah Batu Hampa. In writing this thesis, the type of research that the researcher uses is qualitative descriptive field research which aims to get a picture of something that you want to obtain. The research informants here are PAI teachers as key informants and the school principal as a supporting informant. Data collection techniques in writing this thesis are through interview, observation and documentation techniques. Data analysis techniques in research use steps, namely data reduction, data display, and data verification. The implementation of the independent curriculum learning evaluation in PAI subjects at UPTD SDN 05 Koto Tangah Batu Hampa has been carried out well but in the implementation of the formative assessment there are still obstacles in the initial assessment process. However, the summative assessment is good and in accordance with the assessment plan that has been made.